Comparative analysis of surgical treatment of rhegmatogenous retinal detachment with lower localization of breaks with tamponade of the vitreal cavity by gas or silicone - A.A. Shpak; I.M. Gorshkov; D.O. Shkvorchenko; A.V. Yukhananova (Офтальмохирургия)
Purpose. To perform a comparative evaluation of the efficacy and functional results of surgical treatment of rhegmatogenous retinal detachment (RRD) with breaks in the lower hemisphere using gas or silicone tamponade of the vitreal cavity. Material and methods.Seventy-eight patients (78 eyes) with RRD and the location of breaks in the lower hemisphere were examined. Depending on the nature of retinal detachment patients were divided into 2 groups: without macular detachment («Macula-on») – 36 patients (36 eyes) and with retinal detachment in the macular area («Macula-off») – 42 patients (42 eyes). Each group included two subgroups «Gas» and «Silicone» depending on the type of final vitreal tamponade performed with gas (12% gas-air mixture with perfluoropropane C3F8) or silicone (Densiron), respectively. The type of tamponade was chosen randomly. Results. Subgroups of patients with different types of tamponade did not differ from each other in clinical and demographic characteristics. In the postoperative period, a complete retinal attachment was achieved in 75 patients (96%). At 6 months postoperatively, retinal light sensitivity (total and in central point) in the Macula-on group was significantly higher after treatment with gas tamponade compared to the final tamponade with silicone. For other parameters in the Macula-on group, the type of tamponade did not play a significant role. In the Macula-off group, neither functional parameters nor optical coherence tomography data at 6 months depended on the type of tamponade. Conclusion. The use of tamponade with an air-gas mixture and silicone in RRD patients with localization of breaks in the lower hemisphere is equally effective in achieving a high frequency of retinal attachment. Patients with RRD without macular involvement had significantly higher retinal light sensitivity (total and in central point) after treatment with gas-air tamponade compared to final tamponade with silicone. Gas-air tamponade has the advantage of not requiring a second surgical intervention and can be recommended for wide use in RRD patients with breaks in the lower hemisphere without significant proliferative vitreoretinopathy.